Kelompok wanita nelayan dalam mengolah abon ikan aneka rasa di Kabupaten Konawe Selatan - Sukmawati Abdullah; Bambang Pramono; Wa Nurgayah; Bunyamin Bunyamin (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
PKM activity carried out in Konawe Selatan District aims to introduce various flavors of fish floss to women fishingcommunity and also to improve the production process and business management. Fish is one of the sources of animal proteinthat is easy to consume, cheap and widely consumed by the public. However, because fish can quickly decompose and be easilyperishable, it is needed to process food in order to maintain quality and nutrition. Fish floss with various flavors (original, sweet,and spicy) is believed can diversify fishery products and elevate the economic value of fish which finally can elevate the familyincome. The method of approach used for this PKM is counseling methods and on-the-spot practice of making fish floss and thepackaging to the fisherwomen in Langgapulu village, Kolono district, South Konawe Regency. Moreover, the fisherwomen willbe taught about production and marketing management approach such as management problems of production, and marketingmanagement issues. These activities include theory and practice which includes: (1) extension or counseling of fish floss process;(2) packaging process of fish products, (3) Partnering or inviting media partner, and (4) financing advice. It is hoped that thewoman community in Langgapulu village has knowledge and skills about the micro-business especially fish floss business. Thefisherwomen also know about marketing networks, business media partner or promotion of fish floss products in the form ofbrochure/ leaflet, website, and social media which can help improve the economy of the household.